To simplify the expression \(\sqrt{28} + 3\sqrt{63}\), follow these steps in the correct order:
-
Start with the original expression:
\(\sqrt{28} + 3\sqrt{63}\) -
Factor the square roots: \(\equiv \sqrt{4 \cdot 7} + 3 \sqrt{9 \cdot 7}\)
-
Simplify the square roots: \(\equiv \sqrt{2^2 \cdot 7} + 3 \sqrt{3^2 \cdot 7}\)
-
Use the property \(\sqrt{a^2} = a\): \(\equiv 2\sqrt{7} + 3 \cdot 3\sqrt{7}\)
-
Calculate the coefficients: \(\equiv 2\sqrt{7} + 9\sqrt{7}\)
-
Combine the like terms: \(\equiv (2 + 9)\sqrt{7}\)
-
Final answer: \(\equiv 11\sqrt{7}\)
So, the correct order is:
- \(\sqrt{28} + 3\sqrt{63}\)
- \(\equiv \sqrt{4 \cdot 7} + 3 \sqrt{9 \cdot 7}\)
- \(\equiv \sqrt{2^2 \cdot 7} + 3 \sqrt{3^2 \cdot 7}\)
- \(\equiv 2\sqrt{7} + 3 \cdot 3\sqrt{7}\)
- \(\equiv 2\sqrt{7} + 9\sqrt{7}\)
- \(\equiv 11\sqrt{7}\)
Therefore, the final simplified expression is \(11\sqrt{7}\).